Faktor Dominan Keberhasilan Penyesuaian Sosial Siswa Autis di Sekolah - Tita Adelia Putri; Yusmansyah Yusmansyah; Shinta Mayasari (ALIBKIN (Jurnal Bimbingan Konseling), 2017)
The problem of this study was the social adaptation of children with autism at schools. The research problem was